(untitled) - Mohler, James L. (Clifton Park, N.Y.,Australia,New York, 2006)
Updated to the newest release, Exploring Flash 8 teaches the must have software skills needed to create exceptional Web graphics. The author, examines the tools and features of Macromedia® Flash version 8 and shows how to create vector graphics for the Web. Artwork is expertly woven throughout the information-packed format to drive home key design concepts and show the way to great Web design.
Keywords: Computer animation,Computer graphics,Multimedia systems.,Web site development,Web sites,Đồ họa vi tính,Website